2022
DOI: 10.1039/d2py00643j
|View full text |Cite
|
Sign up to set email alerts
|

Vinylic addition poly(norbornene-co-alkenylnorbornenes) synthesized with benzylic palladium catalysts: materials for manifold functionalization

Abstract: The incorporation of functional groups in the skeleton of vinylic addition polynorbornenes (VA-PNBs) is a difficult task due to the reluctant VA homo- and copolymerization of substituted norbornenes. We have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…developed cationic Pd complexes with η 3 ‐benzyl‐ligand ( Pd63−Pd68 , Figure 17). [14a,78] This ligand can be readily converted to σ‐benzyl‐ligand to recover the benzene ring aromaticity and create an available coordination site on the Pd center. These complexes proved to be effective catalysts for the polymerization of NB , 1.4 , and alkenyl norbornenes ( 1.5 , Figure 4).…”
Section: Cationic Single‐component Palladium Catalysts For Polymeriza...mentioning
confidence: 99%
See 1 more Smart Citation
“…developed cationic Pd complexes with η 3 ‐benzyl‐ligand ( Pd63−Pd68 , Figure 17). [14a,78] This ligand can be readily converted to σ‐benzyl‐ligand to recover the benzene ring aromaticity and create an available coordination site on the Pd center. These complexes proved to be effective catalysts for the polymerization of NB , 1.4 , and alkenyl norbornenes ( 1.5 , Figure 4).…”
Section: Cationic Single‐component Palladium Catalysts For Polymeriza...mentioning
confidence: 99%
“…The nature of metal−C bonds is also essential. For instance, the nature of the allyl group on Pd dramatically affected initiation efficiency and polymer molecular weights [14a,78,81] . Therefore, although no clear guidelines exist for creating a single‐component catalyst with fast initiation and low propagation, systematic tuning of ligands in the metal coordination sphere results in optimal catalyst structural design.…”
Section: Mechanism Of Vinyl‐addition Polymerizationmentioning
confidence: 99%
“…N–N- and N–O-ligated cationic Pd-complexes of a similar structure were found to be single-component catalysts for VAP of unsubstituted norbornenes. , Chen and co-workers showed that a zwitterionic phospine-sulfonate Ni-complex is a latent catalyst for norbornene polymerization . Recently, Pérez-Ortega and Albeniz reported cationic benzylic Pd-complexes as one-component catalysts for VAP . These catalysts showed good catalytic activity and selectivity in VAP of norbornene and alkenylnorbornenes, however, exhibited low activity in the polymerization of polar norbornenes, and were air-sensitive.…”
Section: Introductionmentioning
confidence: 98%
“…53 Recently, Peŕez-Ortega and Albeniz reported cationic benzylic Pd-complexes as onecomponent catalysts for VAP. 54 These catalysts showed good catalytic activity and selectivity in VAP of norbornene and alkenylnorbornenes, however, exhibited low activity in the polymerization of polar norbornenes, and were air-sensitive. Therefore, to the best of our knowledge, there are no singlecomponent catalysts that combine the good activity, tolerance to functional groups, and resistance to oxygen and air moisture, and are capable of catalyzing living VAP of norbornenes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are only a few reports about modifications of VAP polynorbornenes. 12,[17][18][19][20][21][22][23][24] in side chains can enhance the gas permeability and gas separation selectivity of VAP polynorbornenes. In addition, the incorporation of appropriate silyl groups into norbornene-and cycloalkane-based polymers is an effective approach to develop degradable and recyclable thermosets.…”
Section: Introductionmentioning
confidence: 99%